Peningkatan Kecepatan Proses dan Mutu Minyak Bekatul melalui Proses Ekstraksi Berbantukan Ultrasonik - Djaeni, Mohamad; Listyadevi, Yuniar Luthfia (TEKNIK, 2019)
Rice bran oil is one of the oils that has been widely used in the chemical, pharmaceutical and food industries considering the high essential content such as antioxidants, vitamins that are good for the body. Extraction of ultrasonic assisted bran oil is one of many method used to reduce extraction time. The purpose of this study was to examine the effect of extraction methods on mass transfer of bran oil, antioxidant quality, and the quality of bran oil during the extraction process at the temperature, extraction time, and the right solvent ratio. Mass transfer of bran oil was evaluated based on the effect of various temperatures, extraction times, and solvent ratios to predict the right tim e to get a lot of bran oil. Chemical quality (antioxidant content of Î±-tocopherol) and physical quality (oil color) of bran oil were studied so that they were able to predict temperature, extraction time, and relatively good solvent ratio. The results showed that yield increased with increasing temperature and extraction time. However the antioxidant value of Î±-tocopherol will decrease with increasing temperature, extraction time and solvent. The recommended operating conditions for obtaining yields and antioxidant values at 40ÂºC, material to solvent ratio 1: 5 and extraction time for 51 minutes.